2007
DOI: 10.1007/s11783-007-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting simultaneous nitrification and denitrification in an SBBR treating domestic wastewater

Abstract: Recently, researchers have become increasingly interested in the practical application of SND. The reasons are as follows: (1) the products of nitrification including nitrite and nitrate are reactants for nitrification; and (2) the nitrification produces acid and the denitrification produces alkaline. The efficient SND can save money for the construction and operation of wastewater treatment facilities and meet the requirement of carbon resource and alkalinity. Simultaneous nitrification and denitrification in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The thicker biofilm is advantageous for SND. TN removal rate by SND could be 74-82% if suitable operational parameters are adopted and also if influent NH 4 + -N is less than 110 mg/L [5]. It was reported that simultaneous removal of phosphorus and nitrogen was possible in the biofilm SBR as indicated by the respective removal ratio of around 90% and 57% at a COD loading of 1.00 kg COD/m 3 per day [6].…”
Section: Introductionmentioning
confidence: 99%
“…The thicker biofilm is advantageous for SND. TN removal rate by SND could be 74-82% if suitable operational parameters are adopted and also if influent NH 4 + -N is less than 110 mg/L [5]. It was reported that simultaneous removal of phosphorus and nitrogen was possible in the biofilm SBR as indicated by the respective removal ratio of around 90% and 57% at a COD loading of 1.00 kg COD/m 3 per day [6].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al studied mechanism on the nitrogen rich leachate by SBBR, and the ammonia nitrogen removal reached 95% [9]. Factors affecting simultaneous nitrification and denitrification in a SBBR treating domestic wastewater was investigated by Li et al [12], and a concentration of average oxygen range from 0.8 to 4.0 mg/L was proved very efficient for nitrification and denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…In SND, the floc/granule microenvironment provides aerobic conditions towards the exterior favoring nitrification, while denitrification is favored in the interior anoxic zone (Munch et al 1996;Satoh et al 2003). However, the success of this process depends on the conditions prevailing in the reactor (dissolved oxygen (DO), pH, and alkalinity) and diffusion limitations governing transfer of gases, nutrients, and substrate across the flocs/granules (Munch et al 1996;Pochana and Keller 1999;Li et al 2007;Zhang and Zhou 2007). SND may also be achieved using specific strains, such as Thiosphaera pantotropha and Alcaligenes fecalis, that have the ability for heterotrophic nitrification and aerobic denitrification by virtue of their unique enzymes (Robertson and Kuenen 1984a, b;Joo et al 2005;Joo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such strains can overcome the requirement for maintaining critical DO levels and substrate diffusion constrains for denitrification. Some studies have explored nitrogen removal in presence of such strains for low-strength wastewater having NH 4 + -N in the range 20-200 mg L −1 (Gupta and Gupta 1999;Pochana and Keller 1999;Lee et al 2001;Li et al 2007;Zhang andZhou 2007, Morita et al, 2008;Singh and Mittal, 2013) and also wastewater containing nitrophenols in the range 2.5-200 mg L −1 (Kulkarni, 2012;Kulkarni, 2013). However, there are only limited studies on application of such strains for nitrogen removal from highstrength wastewater (Kshirsagar et al 1995;Gupta and Gupta 2001;Joo et al 2005;Joo et al 2006).…”
Section: Introductionmentioning
confidence: 99%